Construction of Covalent Organic Frameworks via Multicomponent Reactions - Guan, Qun; Zhou, Le-Le; Dong, Yu-Bin (Journal of the American Chemical Society, 2023)
Multicomponent reactions (MCRs) combine at least three reactants to afford the desired product in a highly atom-economic way and are therefore viewed as efficient one-pot combinatorial synthesis tools allowing one to significantly boost molecular complexity and diversity. Nowadays, MCRs are no longer confined to organic synthesis and have found applications in materials chemistry. In particular, MCRs can be used to prepare covalent organic frameworks (COFs), which are crystalline porous materials assembled from organic monomers and exhibit a broad range of properties and applications. This synthetic approach retains the advantages of small-molecule MCRs, not only strengthening the skeletal robustness of COFs, but also providing additional driving forces for their crystallization, and has been used to prepare a series of robust COFs with diverse applications. The present perspective article provides the general background for MCRs, discusses the types of MCRs employed for COF synthesis to date, and addresses the related critical challenges and future perspectives to inspire the MCR-based design of new robust COFs and promote further progress in this emerging field.